Protecting, promoting and supporting breastfeeding in all policies: reframing the narrative - Tomori, Cecília (Frontiers in Public Health, 2023)
Recent research highlights the importance of breastfeeding to health across the lifecourse, yet inadequate investment to facilitate breastfeeding according to World Health Organization recommendations threatens to undermine breastfeeding’s protective effects. Western media narratives often fail to convey the significance of breastfeeding, and such narratives can hinder efforts to direct sufficient resources to scaling up effective systems and generating policy change. Delayed action disproportionately harms poor and marginalized communities. The urgency of making these investments in an era of rapidly intensifying climate change and other crises is clear. Reframing the narrative is needed to better appreciate the significance of breastfeeding as well as to recognize and address extensive efforts of undermine it. Evidence-based scientific, health professional and media discussions are necessary to recognize breastfeeding as foundational to food and health security and to enact change so that protecting, promoting and supporting breastfeeding is integrated across all policies.